2007
DOI: 10.1177/019027250707000303
|View full text |Cite
|
Sign up to set email alerts
|

How do We Learn to Trust? A Confirmatory Tetrad Analysis of the Sources of Generalized Trust

Abstract: In this paper we ask whether individuals decide that people are generally trustworthy or untrustworthy by extrapolating from their experiences in localized interactions or whether a more fixed predisposition drives assessments of trustworthiness. These two contrasting theoretical perspectives on generalized trust can be translated into empirically testable models and adjudicated using confirmatory tetrad analysis. This paper is among the first substantive applications of confirmatory tetrad analysis and illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
229
2
13

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(259 citation statements)
references
References 32 publications
15
229
2
13
Order By: Relevance
“…The second strand of related literature deals with general trust. Arguably, modern societies are more then ever based on general trust and social interactions (Simmel 1971;Giddens 1991;Sztompka 1999;Yamagishi 2002;Glanville and Paxton 2007;Klapwijk and Van Lange 2009); without trust societies would disintegrate as trust is a synthetic force within the society (Simmel 1950;Putnam et al 1993). At the same time, general trust turns out to be closely related to bridging social capital while distrust-with bonding social capital; previous findings show that there are mutually reinforcing relationships between social capital and general trust (Growiec 2009(Growiec , 2011.…”
Section: Related Literaturementioning
confidence: 99%
“…The second strand of related literature deals with general trust. Arguably, modern societies are more then ever based on general trust and social interactions (Simmel 1971;Giddens 1991;Sztompka 1999;Yamagishi 2002;Glanville and Paxton 2007;Klapwijk and Van Lange 2009); without trust societies would disintegrate as trust is a synthetic force within the society (Simmel 1950;Putnam et al 1993). At the same time, general trust turns out to be closely related to bridging social capital while distrust-with bonding social capital; previous findings show that there are mutually reinforcing relationships between social capital and general trust (Growiec 2009(Growiec , 2011.…”
Section: Related Literaturementioning
confidence: 99%
“…Contrary to the stability implied by the cultural perspective, the broader class of theories of trust formation referred to as experiential (Dinesen 2012a;Glanville and Paxton 2007) emphasize how trust is formed by experiences throughout life, and thus malleable. Following Putnam's (1993) pathbreaking study, which identified the vitality of civil society as a key explanation of differences in development in the Italian regions, scholars have emphasized participation in voluntary organizations as a prominent explanation in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Social ties and sense of security (Brown et al 2003(Brown et al , 2004Mesch and Manor 1998) are the two most often studied positive social factors. The following variables can be treated as the elements of social ties: number of friends and relatives in neighborhood; interest in family roots and in the history of residence place (Chrząstowski and Lewicka 2008;Connerly 1986;Dawkins 2006;Landale and Guest 1985;Spilimbergo and Ubeda 2004;Wójcik et al 2010); trust in neighbors and trust in close persons (Glanville and Paxton 2007;Portes and Landolt 1996).…”
Section: Social Psychology and Home Biasmentioning
confidence: 99%